2019
DOI: 10.4028/www.scientific.net/ssp.285.398
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Primary α-Al Morphology in Slurry on Segregation during 357 Semi-Solid Die Casting

Abstract: Controlling the morphology of the microstructure of the slurry is important during semi-solid die casting. For this project, semi-solid slugs were produced using the SEED (Swirled Enthalpy Equilibrium Device) process, where a fully liquid metal is poured into a steel crucible and cooled into the semi-solid temperature range, and the crucible and slurry are then swirled and cooled to the appropriate temperature (and solid fraction) for semi-solid casting. The pouring temperature of the melt into the crucible du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…The SEED process is used to produce the initial semi-solid 357.0 aluminium slurries. To avoid the formation of dendritic structure and get a more spherical primary particle, the pouring temperature is set at 630 ℃, which is just above the liquidus (628 ℃, measured by the Differential Scanning Calorimetry (DSC)) [14]. After pouring, the crucible was swirled at 180 rpm for 120 s, and then quenched in water.…”
Section: Methodsmentioning
confidence: 99%
“…The SEED process is used to produce the initial semi-solid 357.0 aluminium slurries. To avoid the formation of dendritic structure and get a more spherical primary particle, the pouring temperature is set at 630 ℃, which is just above the liquidus (628 ℃, measured by the Differential Scanning Calorimetry (DSC)) [14]. After pouring, the crucible was swirled at 180 rpm for 120 s, and then quenched in water.…”
Section: Methodsmentioning
confidence: 99%
“…The pouring temperature plays a crucial role in the size and morphology of α 1 -Al grains, which, in turn, affects their flow behavior and segregation during the die-casting process. Zhang [33] controlled the pouring temperature to obtain grains with different morphologies (dendrites and globular grains) and found that the dendritic structure led to severe segregation in the die-casting parts. Qi [34] investigated the segregation phenomenon of AC46000 castings at different wall thickness locations, where different wall thicknesses represented varying cooling rates.…”
Section: Segregation During Die-castingmentioning
confidence: 99%